2020
DOI: 10.1136/annrheumdis-2020-eular.1505
|View full text |Cite
|
Sign up to set email alerts
|

Op0012 tnf Inhibitors Are Associated With a Reduced Risk of Venous Thromboembolism Compared to Csdmards in Ra Patients

Abstract: Background:While the short-term use of bDMARDs up to 180 days has been associated with an increased risk of venous thromboembolism (VTE) compared to csDMARDs in patients with rheumatoid arthritis (RA), the long term use of more than 730 days has been associated with a decreased risk based on claims data [1]. Among patients with inflammatory bowel disease, observational data indicated that TNF inhibitors may have a protective effect regarding the VTE risk [2].Objectives:To assess the effects of TNF inhibitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
1
0
0
2
Order By: Relevance
“…The observed positive association of genetically-predicted TNF levels with venous thromboembolism is not found in traditional observational studies showing no association [31,32], but the precision was low in those studies. However, a recent longitudinal cohort study based on the German register RABBIT revealed that anti-TNF agents decreased the risk of serious venous thromboembolism events compared to csDMARDs medicine [33], which is in line with our finding. Venous thromboembolism differs in pathology from arterial, which is driven by the atherosclerotic process.…”
Section: Primary Findings In Cardiovascular Diseasesupporting
confidence: 92%
“…The observed positive association of genetically-predicted TNF levels with venous thromboembolism is not found in traditional observational studies showing no association [31,32], but the precision was low in those studies. However, a recent longitudinal cohort study based on the German register RABBIT revealed that anti-TNF agents decreased the risk of serious venous thromboembolism events compared to csDMARDs medicine [33], which is in line with our finding. Venous thromboembolism differs in pathology from arterial, which is driven by the atherosclerotic process.…”
Section: Primary Findings In Cardiovascular Diseasesupporting
confidence: 92%
“…Für TNF-α-Inhibitoren ist belegt, dass sie im Vergleich zu csDMARD eine protektive Wirkung hinsichtlich des Auftretens von Myokardinfarkt und Schlaganfall [ 22 , 23 ] wie auch venösen Thromboembolien haben [ 24 ]. Das heißt, bei RA und SpA reduzieren TNF-α-Hemmer signifikant die Frequenz kardiovaskulärer Ereignisse.…”
Section: Sicherheitsaspekte Der Therapie Mit Bdmardunclassified
“…Dies gilt auch bei erst kurzzeitiger Behandlung mit biologischen DMARDs (ca.6 Monate) im Vergleich zu nicht-biologischen DMARDs. Bei langfristiger Therapie ist das Risiko aber erniedrigt [22]. (Dies sollte vor der RSO mit dem Patienten abgeklärt werden).…”
Section: Thromboseprophylaxeunclassified